O princípio da dignidade da pessoa humana como forma de flexibilizar o critério de deficiência para a concessão dos benefícios assistenciais - Campos, Janaina da Silva Policarpo de (2024)
This research will investigate the relationship between the principle of human dignity and the criteria for granting welfare benefits, focusing on the benefit of continued provision. It will begin with a historical analysis of fundamental rights, highlighting their importance for the Democratic State of Law and their influence on social assistance. The principle of dignity is presented as essential to guarantee minimum subsistence conditions, especially through the benefit of continued provision, which seeks to ensure dignity to those assisted. In addition, other constitutional principles, such as equality, freedom and citizenship, relevant to the granting of welfare benefits, will be discussed. The analysis of disability criteria will consider the flexibility necessary to adapt to different individual situations, with legal basis in the Organic Law of Social Assistance and international guidelines of the World Health Organization. The importance of the continued benefit provision will be highlighted as a guarantee of support for people in vulnerable situations, in line with constitutional principles. Finally, the possibilities of granting welfare benefits will be explored, taking into account the principle of human dignity and the foundations of the Democratic State of Law. This research contributes to the understanding of the importance of making the criteria for granting welfare benefits more flexible, aiming to guarantee the dignity and citizenship of people in vulnerable situations. The deductive and dialectical methodology will be used throughout the research, in addition to the hypothetical-deductive scientific method.